Existence of Periodic Solution for a Nonlinear Fractional Differential Equation. (14th July 2009) - Belmekki, Mohammed; Nieto, Juan J.; Rodríguez-López, Rosana
Abstract : We study the existence of solutions for a class of fractional differential equations. Due to the singularity of the possible solutions, we introduce a new and proper concept of periodic boundary value conditions. We present Green's function and give some existence results for the linear case and then we study the nonlinear problem.